Performance improvements of aluminum foam with different solder compositions via liquid diffusion welding. Issue 8 (18th August 2020) - Yao, C.; Hu, Z.F.; Ren, C.X.; Feng, Y.Q.; Mo, F.
Abstract: Aluminum foam joints were fabricated via liquid diffusion welding with zinc‐aluminum alloy solder aided with ultrasonic vibration at 520 °C. Zinc‐aluminum alloys with different compositions (10 % aluminum, 20 % aluminum, 30 % aluminum) were used as solder material. The control group was fabricated under the same conditions but without ultrasonic assistance. The microstructure of aluminum foam joints was analyzed by optical microscopy, scanning electron microscopy, and energy dispersive spectroscopy. Among the different soldering alloys, those with the zinc‐20aluminum solder had the widest diffusion area and the most continuous interface. The tensile strength of metallurgic alloy joined aluminum foams was tested. Zn20Al samples had the best performance among all samples, including the low‐density substrate aluminum foam (0.3 g/cm 3 and 0.4 g/cm 3 ), but it still showed a lower performance than the high‐density substrate aluminum foam (0.6 g/cm 3 ). Therefore, ultrasonic vibration remarkably improved the tensile strength and impact toughness of joints. Samples with ultrasonic assistance had better tensile strength and impact toughness than high‐density substrate aluminum. Abstract : Metallurgic‐ally joined aluminum foam are successfully fabricated via the hot dipping and hot pressing process. The fusions of the three aluminum‐zinc alloys in joint area are all compact and continuous without evident macroscopic defects. The aluminum area has a distinct transition layer and the alloy structure has a relatively close network structure.